![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\frac{x}{5}-\frac{2}{3}+2x=\frac{1}{2}\)
\(\frac{6x}{30}-\frac{20}{30}+\frac{60x}{30}=\frac{15}{30}\)
\(\frac{66x-20}{30}=\frac{15}{30}\)
\(\Rightarrow\) 66x - 20 = 15
66x = 15 + 20
66x = 35
x = \(\frac{35}{66}\)
Vậy x = \(\frac{35}{66}\)
b, \(\frac{5}{2}-3\left(\frac{1}{3}-x\right)=\frac{1}{7}\)
\(\frac{5}{2}-1+3x=\frac{1}{7}\)
\(\frac{3}{2}+3x=\frac{1}{7}\)
3x = \(\frac{1}{7}-\frac{3}{2}\)
3x = \(\frac{-19}{14}\)
x = \(\frac{-19}{42}\)
Vậy x = \(\frac{-19}{42}\)
Phần c lỗi, chắc như thế này
c, \(4\cdot\left(\frac{1}{2}-x\right)+\frac{1}{2}=\frac{-5}{6}+x\)
\(2-4x+\frac{1}{2}=\frac{-5}{6}+x\)
\(\frac{5}{2}-4x=\frac{-5}{6}+x\)
\(-4x-x=\frac{-5}{6}-\frac{5}{2}\)
\(-5x=\frac{-10}{3}\)
x = \(\frac{2}{3}\)
Vậy x = \(\frac{2}{3}\)
Chúc bn học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\frac{5}{3}-\frac{2}{3}\times x=1\)
=>\(\frac{2}{3}\times x=\frac{5}{3}-1\)
=>\(\frac{2}{3}\times x=\frac{2}{3}\)
=>\(x=\frac{2}{3}:\frac{2}{3}\)
=>\(x=1\)
b)\(\frac{1}{2}+\frac{5}{7}:x=\frac{1}{6}\)
=>\(\frac{5}{7}:x=\frac{1}{6}-\frac{1}{2}\)
=>\(\frac{5}{7}:x=-\frac{1}{3}\)
=>\(x=-\frac{1}{3}\times\frac{5}{7}\)
=>\(x=-\frac{5}{21}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
b) /x-1/=0
x-1=0
x=1
Vậy x=1
c) 2./x-3/=6
|x-3|=3
\(\Rightarrow\orbr{\begin{cases}x-3=3\\x-3=-3\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x=6\\x=0\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(x+1\right)-\frac{x+1}{3}=\frac{5\left(x+1\right)-1}{6}\)
\(\Leftrightarrow6\left(x+1\right)-2\left(x+1\right)=5\left(x+1\right)-1\)
\(\Leftrightarrow6x+6-2x-2=5x+5-1\)
\(\Leftrightarrow6x-2x-5x=5-1-6+2\)
\(\Leftrightarrow-x=0\)
\(\Leftrightarrow x=0\)
b) \(\left(1-x\right)^2+\left(x+2\right)^2=2x\left(x-3\right)-7\)
\(\Leftrightarrow1-2x+x^2+x^2+4x+4=2x^2-6x-7\)
\(\Leftrightarrow2x^2+2x+5=2x^2-6x-7\)
\(\Leftrightarrow2x+6x=-7-5\)
\(\Leftrightarrow8x=-12\)
\(\Leftrightarrow x=-\frac{3}{2}\)
c) \(2+\frac{x-2}{2}-\frac{2x-4}{3}-\frac{5}{6}\left(2-x\right)=0\)
\(\Leftrightarrow2+\frac{x}{2}-1-\frac{2}{3}x+\frac{4}{3}-\frac{5}{3}+\frac{5}{6}x=0\)
\(\Leftrightarrow\frac{x}{2}-\frac{2}{3}x+\frac{5}{6}x=-2+1-\frac{4}{3}+\frac{5}{3}\)
\(\Leftrightarrow\frac{2}{3}x=-\frac{2}{3}\)
\(\Leftrightarrow x=-1\)